2003
DOI: 10.1002/ptr.1134
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antiprotozoal and antioxidant activity of five plants used in Izabal for infectious diseases

Abstract: Methanol and aqueous extracts from fi ve plant species, used in traditional medicine in Guatemala for the treatment of microbial infections, were tested in vitro for their ability to scavenge DPPH, OH(.) and O(2) (-) radicals and to inhibit lipoperoxidation (LPO) in order to establish a relationship between their antioxidant activities and their effects against infectious agents. Acalypha guatemalensis, Ocimum micranthum and Smilax spinosa possessed a significant activity against both the three free radicals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…An antioxidant effect was also described for Guazuma ulmifolia Lam. (Sterculiaceae) (Navarro et al, 2003). Finally, as seen in Table 3, the remaining seven species possess effects which also do not match the Quilombola indication.…”
Section: For Rejuvenationmentioning
confidence: 84%
See 1 more Smart Citation
“…An antioxidant effect was also described for Guazuma ulmifolia Lam. (Sterculiaceae) (Navarro et al, 2003). Finally, as seen in Table 3, the remaining seven species possess effects which also do not match the Quilombola indication.…”
Section: For Rejuvenationmentioning
confidence: 84%
“…On the other hand, a poisonous effect on cattle (Barth et al, 1994) and mosquito repellent action (Palsson and Scientific studies found in literature for 11 of the 31 species cited by the Quilombolas (with a possible effect on the CNS). In four species marked with an asterisk (*), Quilombola use bears some resemblance to the effects/action described in the pharmacological studies Martins et al, 1994Carbajal et al, 1989Palmieri, 2000Mattei et al, 2001Galvão et al, 2002Morales et al, 2001Vilegas et al, 1993Aguiar et al, 1988Trovato et al, 1996Silva et al, 1985Navarro et al, 2003Hor et al, 1995Solon et al, 2000;Menezes, 2002Barth et al, 1994Palsson andJaenson, 1999 Ruppelt et al, 1991 Jaenson, 1999) were described for Senna occidentalis (L.) Link (Fabaceae). An antioxidant effect was also described for Guazuma ulmifolia Lam.…”
Section: For Rejuvenationmentioning
confidence: 90%
“…For example, an ethanolic extract of leaves of Piper betle (Sarkar et al 2008), the 2',6'-dihydroxy-4'-methoxychalcone isolated from the inflorescence of Piper aduncum (Caio et al 1999) and kavapyron from leaves of Piper rusbyi (Flores et al 2007) all showed in vitro activity against Leishmania. However, previous studies have reported that an aqueous and methanolic extract from the leaves of P. auritum did not show any activity against promastigotes of L. mexicana and L. braziliensis (Navarro et al 2003). Although people commonly use infusion or beverages derived from herbs, there has been a resurgence of interest in essential oils, which are oily liquids obtained from plant material.…”
Section: Discussionmentioning
confidence: 99%
“…22 The anti-diabetic properties, 23 hypotensive and vasorelaxant activity, 24 antiulcer, 25,26 anti-bacterial activities, 20,27 and antiviral activity 28 of the bark, aerial parts, fruits, crude extract, and fractions were attributed to the presence of proanthocyanidins.…”
Section: Introductionmentioning
confidence: 99%